Implicit Euler Discretization for Enhanced Sliding Mode Observer in Sensorless Permanent Magnet Synchronous Motor Control - Nehal Baiomy; Mohamed Mahmoud Abdelhafiz; Abdelmomen Mahgoub (IEEE Access, 2025)
This paper presents a discrete-time sliding mode observer designed to estimate the rotor position of PMSMs for sensorless control strategies. Without compromising the sliding feature, this study employs a discretization method known as implicit Euler discretization, converting the set-valued function to a projection over a limited interval, simplifying the coding compared to other ordinary implementations. As a result, output chatter is significantly reduced without additional filters. The observer’s performance is evaluated under sudden changes in load and parameter variations and then compared with other approaches. The proposed SMO is also tested and validated on an experimental setup of a 600W PMSM coupled with a DC generator for loading. The results show the robustness of the proposed observer, with a reduction in execution time by approximately 20% compared to conventional implementations like the sigmoid-based sliding mode observer.